2018
DOI: 10.1016/j.atherosclerosis.2018.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Human mast cell neutral proteases generate modified LDL particles with increased proteoglycan binding

Abstract: The present study suggests that cathepsin G in human atherosclerotic lesions is largely derived from MCs and that activated MCs may contribute to atherogenesis by enhancing LDL retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 53 publications
(51 reference statements)
1
19
0
Order By: Relevance
“…Issues related to specificity likely include the small increases in sAT concentrations occurring with random variations or nonanaphylactic events, and mechanisms of anaphylaxis that do not involve MC degranulation . Indeed, MC activation has been reported in atherosclerosis‐related cardiovascular events, coagulation abnormalities, and response to infectious agents . In line with previous cohorts, our results confirm that the consensus algorithm sAT >([1.2 × sBT] + 2) μg/L is a good compromise between empirical thresholds such as >(1.35 × sBT), which privileged sensitivity as high as 0.91 in previous literature and 0.81 in our study, or (sBT + 3) μg/L, which resulted in sensitivity values as low as 0.63 in the literature and 0.72 in our hands.…”
Section: Discussionsupporting
confidence: 84%
“…Issues related to specificity likely include the small increases in sAT concentrations occurring with random variations or nonanaphylactic events, and mechanisms of anaphylaxis that do not involve MC degranulation . Indeed, MC activation has been reported in atherosclerosis‐related cardiovascular events, coagulation abnormalities, and response to infectious agents . In line with previous cohorts, our results confirm that the consensus algorithm sAT >([1.2 × sBT] + 2) μg/L is a good compromise between empirical thresholds such as >(1.35 × sBT), which privileged sensitivity as high as 0.91 in previous literature and 0.81 in our study, or (sBT + 3) μg/L, which resulted in sensitivity values as low as 0.63 in the literature and 0.72 in our hands.…”
Section: Discussionsupporting
confidence: 84%
“…HuChem-156 is produced by cathepsin G, chymase or kallikrein 7 from huChem-163 [ 1 ]. These proteases are expressed by mast cells, which contribute to liver fibrosis and HCC [ 40 , 41 , 42 ]. Whether huChem-156 is abundant in human liver needs further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Cleavage of VE-cadherin mediated by elastase, one of the proteases associated with NETs, abolishes cell–cell contacts and increases cell permeability (64). Recent evidence demonstrated that cathepsin G, which is also a NETs-associating protease, mediates the degradation of apoB in native LDL to cause LDL fusion and enhanced binding of LDL to isolated human aortic proteoglycans and human atherosclerotic lesions ex vivo , thereby contributing to atherogenesis (65, 66). Interestingly, it is presumable that cooperative pathophysiological relevance of proteases on NETs and lipoproteins causes the progression of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%